Analisis Strategi Pengelolaan Wakaf Uang di Indonesia (Pendekatan Metode Delphi) - Hendri Tanjung; Tjetjep Suhandi; Widdy Tanzila (Prodi Perbankan Syariah FAI UMT, 2020)
Potential cash waqf in Indonesia is enormous. However, the fact that management of waqf money is still encountering many obstacles. This study tried to identify priority constraints become a bottleneck in the management of cash waqf in Indonesia, following the priority solution that can be offered in support of the management of cash waqf in Indonesia with the approach of the Delphi method. Delphi method is a systematic method of collecting opinions from a group of expert withdrawal through a series of questionnaires based linkert scale. Based on the analysis of Delphi that rank highest priority constraint is the lack of public understanding of the waqf money followed by lack of public awareness to be charitable. The results of the analysis of Delphi that ranked highest strategic priorities with the acquisition of the average value of the same magnitude, there are three criteria, namely to provide effective education and outreach to the community about cash waqf, an innovative marketing strategy of waqf institutions, as well as the transparency and accountability of waqf institutions. It is expected that the joint commitment of various parties, academics, practitioners and policymakers in boosting cash waqf management efforts in Indonesia